Muslim Consumer Preferences in Cirebon Toward Halal Certified Food Products - Safitri, Eka; Sumarmi, Sumarmi; Sinaga, Sunita; Fega, Nabila; Sa'dudin, Ihsan; Herlina, Nina (Indonesian Journal of Food Technology, 2025)
This study aims to understand how the preferences of Muslim consumers in Cirebon toward halal-certified products are influenced by the prevailing social, cultural, and religious values within their communities. Using a socio-anthropological approach and the theory of innovation adoption, this research examines the social processes shaping halal consumption decisions and how halal products are selected not only for religious reasons but also as expressions of social identity. The research employs a qualitative method with a mini ethnographic approach, including in-depth interviews with consumers, participant observation, and documentation in both urban and rural areas of Cirebon. The key findings reveal that families, Islamic boarding schools (pesantren), and religious organizations play significant roles as agents of change in promoting the adoption of halal products. Moreover, innovation characteristics such as observability and trialability emerge as critical factors in encouraging acceptance, especially when supported by trusted community or religious figures. The novelty of this study lies in uncovering that preferences for halal products are not solely driven by individual religious consciousness, but also by social pressure and a desire to maintain collective Muslim identity in Cirebon. Academically, this research contributes to a deeper understanding of innovation adoption dynamics within religious and cultural contexts and offers a new perspective on halal certification as a symbolic marker of morality and identity. It also provides a theoretical and practical foundation for developing more culturally contextualized halal education strategies.